Harnessing the Power of Artificial Intelligence: An In-Depth Review of its Effective Role in Countering Violent Extremism - Muhammad Ansar Naseer; Ghazala Shaheen (JURIHUM : Jurnal Inovasi dan Humaniora, 2023)
The article "Effective Role of AI in Countering Violent Extremism" explores how Artificial Intelligence (AI) can be a game changer in the fight against the ubiquitous menace of violent extremism in the digital era. This review article thoroughly explains the topic by navigating many aspects of AI's rolthwartinghwart extremist ideology and actions. The paper starts by examining the critical role that artificial intelligence (AI) plays in content analysis, wherein image analysis and natural language processing (NLP) tools enable authorities to trace patterns of radicalization, identify extremist content, and stop the spread of extremist propaganda. It then delves into the al media monitoring and analysis, showcasing how AI-driven systems enable real-time surveillance of social platforms to identify extremist activities, track the spread of extremist narratives, and detect anomalies that may signal impending threats. The paper elucidates the significance of predictive modeling. AI modeling, AI-powered predictive modeling, and early warning systems harness learning algorithms to anticipate potential extremist threats, allowing for proactive intervention by law enforcement agencies. The review underscores the diversity of data sources and the training of models on historical data, along with the ethical considerations that underpin the underpinning these systems’ use take center stage in the subsequent section, where the paper underscores the need to strike a balance between security and individual rights. It probes into the ethical intricacies of privacy violations, algorithmic fairness, freedom of expression, and the suppression of dissent as AI is deployed in countering extremism. The review underscores the importance of transparency, accountability mechanisms, and legal frameworks to guide the responsible use of AI in this domain. The paper proceeds to offer real-world case studies and success stories that underscore the tangible impact of AI in disrupting extremist networks, preventing radicalization, and enhancing public safety. These cases include content removal algorithms on social media platforms, predictive policing programs, advanced network analysis techniques, and online extremism prevention initiatives driven by AI. Subsequently, the article investigates the array of challenges and limitations AI confronts when countering challenges such as algorithm accuracy, ethical dilemmas, regulatory hurdles, resource constraints, and legal complexities, providing a nuanced understanding of the multifaceted landscape.